Britain and the EU : in or out? (Financial Times, 2013)
Britain has had an ambivalent attitude to the European Union ever since it joined 40 years ago. So what does prime minister David Cameron's promise to hold a referendum on whether the UK should stay in the union mean' What would a "Brexit" entail for Britain, Europe, and the world' These are the questions answered in Britain and the EU, an ebook of 10,000 words, compiled from news and comment published in the Financial Times, the global business newspaper which combines expert UK political coverage with unrivalled reporting on the European Union. The ebook's publication in April 2013 comes less than a year after the runaway success of the FT's first ebook, If Greece goes ... which looked at the consequences of Athens' feared expulsion from the eurozone.